LOCAL NATIONAL SCHOOLS AND PERIODICAL PUBLICATIONS OF TURKESTAN IN THE BEGINNINGXX CENTURY - Feruza Aminovna Turakulova (Galaxy International Interdisciplinary Research Journal, 2023)
The article displays information about the changes made to the traditional education system of the local population of Turkestan at the beginning of the 20th century, the implementation of policies in the education system that met the interests of the colonial authorities, the opening of schools belonging to Russian nationality and the rapid growth of their number.